2016
DOI: 10.13065/jksdh.2016.16.02.295
|View full text |Cite
|
Sign up to set email alerts
|

Influence of denture wearing on a mini-mental state examination(MMSE-K) in the elderly

Abstract: Objectives:The purpose of the study was to investigate the association between denture wearing and dementia using a Mini-Mental State Examination (MMSE-K) in the community dwelling elderly. Methods: The study subjects were 184 community dwelling elderly using Korean version of mini-mental state examination(MMSE-K). The variables included the general characteristics of the subjects, denture earing, number of mastication tooth, subjective mastication ability, and MMSE(dementia). Denture wearing was divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Cho et al . found that patients with natural dentition had better cognitive ability (i.e., a higher Mini-Mental State Examination score) than those with removable dentures 11 . Poor oral health in the elderly has been reported to be strongly associated with dementia 811 ; however, oral health is still considered to be separate from and less important than systemic health 12 .…”
Section: Introductionmentioning
confidence: 97%
“…Cho et al . found that patients with natural dentition had better cognitive ability (i.e., a higher Mini-Mental State Examination score) than those with removable dentures 11 . Poor oral health in the elderly has been reported to be strongly associated with dementia 811 ; however, oral health is still considered to be separate from and less important than systemic health 12 .…”
Section: Introductionmentioning
confidence: 97%
“…Thus, we believe that a study that focuses on the relationship between mortality and various oral health-related indicators, such as tooth number, should be conducted in the future for more conclusive results. Furthermore, the association between masticatory disorder and mortality needs to be assessed through community-based cohort studies, after controlling for nutritional problems caused by systemic diseases 34 37 , and psychological factors 38 .…”
Section: Discussionmentioning
confidence: 99%
“…2011년부터 전 국 보건소에서 치매 조기검진 사업용으로 사용되고 있으며 점수는 최대 0점에서 30점으로 점수가 낮을수록 인지기능 의 저하가 있는 것으로 판정한다 13) . 치매와 구강건강과의 관련성에 관한 국내 연구는 보건소 사업과 연관해서 연구 가 실행되었기 때문에 대부분 MMSE 설문을 사용하고 있 다 [14][15][16] .…”
Section: 서 론unclassified